2009
DOI: 10.1007/s11270-009-0150-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Potential of Forest Species Under “Microbial Management” for the Restoration of Degraded Mining Areas

Abstract: The increasing number of degraded soil areas caused by open cast mining activities has brought about a critical damage to the environment. The mine spoil must be ameliorated with anthropogenic interferences which consist of revegetating soils after organic matter amendment and provision of microbial diversity, to guarantee basic conditions for a sustainable soil biological activity. Five woody species, Acacia mangium Willd., Inga edulis Mart., Mimosa caesalpiniaefolia Benth, Parkia multijuga Benth., and Schinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…To our knowledge, no study has yet designed spatially explicit experiments that could formally demonstrate the role of fungi in driving the spatial distribution of plant species. This would require the manipulation of fungal communities in the field, either with fungal-addition treatments (Mendes et al, 2010), fungal-removal treatments using fungicides (Helgason et al, 2007), or a combination of both. However, field manipulation of micro-organisms is challenging and complementary correlative approaches such as used here will likely remain valuable to garner information on plant-fungi interactions at wider spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has yet designed spatially explicit experiments that could formally demonstrate the role of fungi in driving the spatial distribution of plant species. This would require the manipulation of fungal communities in the field, either with fungal-addition treatments (Mendes et al, 2010), fungal-removal treatments using fungicides (Helgason et al, 2007), or a combination of both. However, field manipulation of micro-organisms is challenging and complementary correlative approaches such as used here will likely remain valuable to garner information on plant-fungi interactions at wider spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…Ignoring seasonal effects, AMF colonization was always higher in A. mangium monoculture and intercropped plantations (AMS and EMS), since this is a highly mycotrophic species (Mendes-Filho et al, 2009). According to Ghosh and Verma (2006), Acacia seedlings inoculated with AMF (Glomus mosseae, G. occultum and G. aggregatum) show an increase in shoot dry matter, root diameter, leaf area, chlorophyll content and biomass of A. mangium, when compared with the non-inoculated control plants.…”
Section: Amf Colonizationmentioning
confidence: 98%
“…Though both species, E. grandis and A. mangium, can associate either with AMF or with ectomycorrhizal fungi (Mendes-Filho et al, 2009;Pagano et al, 2008), our studies were restricted to the first group, since our observations refer to very young plants, beginning at the seedling stage, a period in which there is a predominance of AMF colonization in the roots of both plants (Adams et al, 2006;Pagano and Scotti, 2008). However, very little is known about the association between AMF and Eucalyptus, especially when intercropped with A. mangium, which is characterized by forming symbioses with Nfixing bacteria and AMF (Mendes-Filho et al, 2009). Intercropped systems generally show greater diversity and abundance of AMF than pure stands (Pagano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Coalmine degraded lands are reclaimed by planting drought resistant, fast growing trees without considering their ameliorative properties. Different tree species have varying degree of ameliorative affect on mine soils (Mukhopadhyay and Maiti, 2011;Juwarkar et al, 2010;Mendes Filho et al, 2010;Sinha et al, 2009;Dutta and Agrawal, 2003). Yao et al (2010) studied the improvement in physicochemical properties of a 15-year old reclaimed coal mine soils (Inner Mongolia, China) and concluded that different tree species have varying degree of influence on soil forming process.…”
Section: Introductionmentioning
confidence: 99%